Gender-related family head schooling and Aedes aegypti larval breeding risk in Southern Mexico - Danis-Lozano Rogelio; Rodríguez Mario H; Hernández-Avila Mauricio (Instituto Nacional de Salud Pública, 2002)
Objective. To investigate if family head genre-associated education is related to the risk of domiciliary Aedes aegypti larval breeding in a dengue-endemic village of Southern Mexico. Material and Methods. A family head was considered to have a low education level if he/she had not completed elementary school. To estimate larval breeding risk within each household, a three-category Maya index was constructed using a weighted estimation of controllable and disposable domestic water containers. A socio-economic index was constructed based on household construction characteristics. Results. Low-level education of either family head was associated to higher larval breeding risk. Households with low-educated mothers had more larval breeding containers. These associations persisted after adjusting for household socio-economic level. Conclusions. These results indicate that households with female family heads with low education levels accumulate more containers that favor Ae. aegypti breeding, and that education campaigns for dengue control should be addressed to this part of the population.